Analisis Penyajian Konsep Fungsi pada Buku Teks Matematika Singapura dalam Mengembangkan Berpikir Kritis - Nursidrati; Lala Intan Komalasari; Sofyan Syamratulangi (Jurnal LENTERA: Jurnal Studi Pendidikan, 2022)
The purpose of this study was to describe the form of the presentation of function concepts in Singapore mathematics textbooks as well as the potential for presenting the concept of function in developing critical thinking skills. This study uses descriptive qualitative research methods. Data sources were obtained from Singapore mathematics textbooks written by Dr. Joseph Yeo, Loh Cheng Yee, Teh Keng Seng, Neo Chai Meng, Ivy Chow, and Jacinth Liew under the consultation of Dr. Yeap Ban Ha entitled New Syllabus Mathematics Edition r. The critical thinking criteria used were adapted from the critical thinking criteria set by Facione (2015), which consisted of interpretation, analysis, evaluation, and inference. The results of the study show that the presentation of the concept of function in Singapore mathematics textbooks is presented deductively through investigative activities. While the potential presentation of function concepts in Singapore mathematics textbooks in developing critical thinking skills fulfills all aspects of predetermined critical thinking, namely interpretation, analysis, evaluation, and inference. This shows that the presentation of functional concepts in Singapore mathematics textbooks can develop critical thinking skills.